1997
DOI: 10.1046/j.1365-2672.1997.00372.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and isolation of a bactericidal domain in chicken egg white lysozyme

Abstract: Chicken egg white lysozyme exhibits antimicrobial activity against both Gram‐positive and Gram‐negative bacteria. Fractionation of clostripain‐digested lysozyme yielded a pentadecapeptide with antimicrobial activity but without muramidase activity. The peptide was isolated and its sequence found to be I‐V‐S‐D‐G‐N‐G‐M‐N‐A‐W‐V‐A‐W‐R (amino acids 98–112 of chicken egg white lysozyme). A synthesized peptide of identical sequence had the same bactericidal activity as the natural peptide. Replacement of Trp 108 with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(96 citation statements)
references
References 1 publication
4
90
1
1
Order By: Relevance
“…These domains are thought to be natural enzymatic digestion products of larger molecules, perhaps consumed and degraded in the intestinal tract. These include lysosome residues 98 through 112 [99], a lactoferrin fragment called lactoferricin [100 Á/104] and hen ovotransferrin residues located within the 109Á/ 200 sequence of the N-terminus [105]. These studies suggest that ingested bovine lactoferrin is partially degraded by gastric contents to antimicrobial fragments containing the lactoferricin region [103].…”
Section: Peptides As Fragments Of Larger Proteinsmentioning
confidence: 86%
“…These domains are thought to be natural enzymatic digestion products of larger molecules, perhaps consumed and degraded in the intestinal tract. These include lysosome residues 98 through 112 [99], a lactoferrin fragment called lactoferricin [100 Á/104] and hen ovotransferrin residues located within the 109Á/ 200 sequence of the N-terminus [105]. These studies suggest that ingested bovine lactoferrin is partially degraded by gastric contents to antimicrobial fragments containing the lactoferricin region [103].…”
Section: Peptides As Fragments Of Larger Proteinsmentioning
confidence: 86%
“…Alternatively, lysozyme at later stages of development may undergo enzymatic hydrolysis by certain proteases that produce fragments of the enzyme with enhanced activity. It has been shown that the hydrolysis of lysozyme by different proteolytic enzymes, such as clostripain, pepsin and trypsin, caused the exposure of the antibacterial peptides of the enzyme, and as a result increased its antibacterial activity (Pellegrini et al 1997;Ibrahim et al 2001Ibrahim et al , 2002Ibrahim et al , 2005Mine et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Lysozyme demonstrates antimicrobial activity against a limited spectrum of bacteria and fungi [60]. However, the antimicrobial activity of lysozyme is greater for certain Grampositive bacteria.…”
Section: Lysozymementioning
confidence: 99%
“…Enzymatic hydrolysis of lysozyme is a novel technology that uses proteolytic enzymes for hydrolyzing native lysozyme to produce potent antimicrobial peptides that hidden within its folds. Lysozyme was digested by different proteolytic enzymes, such as clostripain [58,60], pepsin, and trypsin [97,98,99]. All these researchers proved that the resulting peptides lost the enzymatic activities of lysozyme, but exhibited strong bactericidal activities against both Gram-negative (E.coli, Salmonella, Pseudomonas, and Aeromonas) and Gram-positive bacteria (Listeria monocytogenes, Staph aureus, Bacillus spp., and Leuconostics spp.)…”
Section: Lysozyme Peptidesmentioning
confidence: 99%